Penerapan Metode Hybrid Multi Criteria untuk Penilaian Mahasiswa Berprestasi - Rizal Furqan Ramadhan (Universitas Wahid Hasyim, 2024)
Higher education is an educational institution that educates students as objects of education to be prepared for the world of work by being equipped with theoretical and practical skills. With increasingly tough demands and intense competition in finding work, it is necessary to assess students regarding the academic and non-academic activities they participated in and pursued while still in college. With the rapid movement of information technology, an assessment of student achievement can be implemented using an information technology system using the Decision Support System concept with multi-criteria techniques. The Decision Support System has a basic function to simplify and assist leaders or managers in making decisions. The decision in this research topic is outstanding students. The research uses the Hybrid Multi Criteria method. Hybrid is a combination of 2 methods in the system but runs according to their respective functions. The 2 multi-criteria hybrid methods applied include Simple Additive Weighting and Weighted Sum Model. The data used is 22 students from UIN Sayyid Ali Rahmatullah Tulungagung. The results of the two methods are almost the same, namely MHS8 and MHS10 are in the first and second positions respectively, then for the third position and so on there are differences between the two Hybrid methods. Based on the output results from the Hybrid Multi Criteria method, it can be concluded that the Simple Additive Weighting and Weighted Sum Model methods are ideal for helping provide decisions to leaders in a university to decide which students fall into the achievement category.